2022
DOI: 10.3390/jcm11195501
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lightweight Approach to COVID-19 Diagnostics Based on Chest X-ray Images

Abstract: Background: This paper presents a novel lightweight approach based on machine learning methods supporting COVID-19 diagnostics based on X-ray images. The presented schema offers effective and quick diagnosis of COVID-19. Methods: Real data (X-ray images) from hospital patients were used in this study. All labels, namely those that were COVID-19 positive and negative, were confirmed by a PCR test. Feature extraction was performed using a convolutional neural network, and the subsequent classification of samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The method was evaluated on a pre-prepared hospital dataset available at https://github.com/UTP-WTIiE/Xray_data.git and previously described and used in [ 9 ]. Images from this dataset are anonymized, realistic data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was evaluated on a pre-prepared hospital dataset available at https://github.com/UTP-WTIiE/Xray_data.git and previously described and used in [ 9 ]. Images from this dataset are anonymized, realistic data.…”
Section: Methodsmentioning
confidence: 99%
“…The images were provided in a raw form, without masks. The dataset was introduced and described in [ 9 ]. Each model in this research was evaluated using 4 validation metrics as follows: accuracy ( Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Study [30] introduces an innovative and lightweight machine learning-based approach aimed at facilitating the diagnosis of COVID-19 through the analysis of X-ray images. The proposed method offers a rapid and effective means of diagnosing COVID-19 based on medical imaging.…”
Section: Applications Of Image Analysis In Musculoskeletal Imagingmentioning
confidence: 99%
“…CatBoost [7] is a gradient boosting decision tree (GBDT) variant that is highly scalable and robust for medical anomaly detection and capable of handling a wide range of medical data features to improve detection accuracy and efficiency. Empirical studies have shown that CatBoost exhibits higher accuracy and a lower false alarm rate than other algorithms in arrhythmia detection and lung X-ray image lesion detection and is able to quickly and accurately identify new crown lesions [8] .…”
Section: Introductionmentioning
confidence: 99%